External And Internal Factors Analysis For “Mining Contractors Services Company” In Indonesia - Andrea Sigit Sulaksono; Edi Hamdi (Cakrawala Repositori IMWI, 2023)
Background - Coal Production, The Ministry of Energy and Mineral Resources (ESDM) noted that Indonesia's coal production will reach 606.22 million tons in 2021 from the planned 625 million tons or 96.99%. An increase of 7.2% compared to 2020 of 565.69 million tones. Since 2014, coal production has shown an increasing trend. However, production declined in 2016 and 2020. In 2016, coal production fell 1.1%, while in 2020, production fell 8.2%. The Ministry of Energy and Mineral Resources estimates that Indonesia's coal production in 2022-2023 will increase in the range of 637 million tons to 664 million tons. Meanwhile, the demand for domestic coal (domestic market obligations/DMO) in 2021 is 63.47 million tons or 10% of total production has been realized. The figure decreased by 51.87% from 131.89 million tons in 2020.